"Enhancement of solubility of a poorly soluble antiplatelet aggregation drug by cogrinding technique" - Bayoumi, Asmaa A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The goal of this study was to formulate ticagrelor tablets with enhanced dissolution rate using cogrinding technique. However, it belongs to the biopharmaceutical classification system Class IV molecule, poorly soluble, and permeable. Methods: Various ratios (0.2:1–1.67:1) of povidone (PVP)/drug were used in the formulations. Ticagrelor was coground with different percentage of PVP K 25 (carrier) in a mortar with a pestle for 30 min, then mixed with the rest excipients. A high-performance liquid chromatography stability indicating assay was developed to test the stability of ticagrelor in the selected formulae. Results: The results showed that the presence of PVP in relatively high ratios compared to the drug is desirable for enhancing the dissolution rate of ticagrelor. The best-optimized formulae found were that F8 and F9 which showed good disintegration and dissolution rate of ticagrelor more than 92% after 30 min while the dissolution rate for ticagrelor standard was only 22% after 30 min. Stability studies were performed on the selected formulae F8 and F9. Conclusion: The optimized formulae were evaluated for thickness, weight variation, hardness, friability, dissolution, and accelerated stability study for a period of 6 months. Cogrinding using PVP K 25 proved to enhance the dissolution of ticagrelor which may be due to the formation of a soluble complex between ticagrelor and PVP. The selected formulae F8 and F9 showed good stability.